How does weather and climate affect pedestrian walking speed during cool and cold seasons in severely cold areas?. (15th May 2020) - Liang, Shuai; Leng, Hong; Yuan, Qing; Wang, Biwei; Yuan, Chao
Abstract: Being able to understand pedestrians behavior is essential for urban planning. Despite a burgeoning research effort directed at the design and modelling of effective urban spaces for pedestrians, remarkably little is known about how pedestrians actually negotiate urban spaces in severely cold areas. By adopting computer vision technology, this paper reports the results of a video-based observational study aimed at exploring how and to what degree weather and climate affect pedestrian walking speed. The result shows that ice-snow sports, as a source of space attraction, can trigger a sudden change in the walking speed of pedestrians within space at the level of personal willingness. It also shows that the average walking speed at population level, was affected by both apparent temperature and ground conditions. Specifically, the average walking speed is negatively correlated with the instantaneous apparent temperature. The apparent temperature also has a time-lag effect on the average walking speed and the larger the temperature fluctuation, the more significant the time-lag effect. When the ground covered with snow, the average walking speed will decrease by about 0.102 m/s than that of the clean ground. These findings, we hope, should prove useful to any researcher and urban manager interested in and committed to designing more effective pedestrian spaces and in modelling pedestrian behavior at a microscopic level in harsh climate. Highlights: Computer vision technology was used to detect pedestrian behavior. The average walking speed can be affected by apparent temperature. The apparent temperature has a time-lag effect on the average walking speed. Ground covered with snow will slow down the average walking speed.